Rapid Spread of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Omicron Subvariant BA.2 in a Single-Source Community Outbreak. (10th March 2022) - Cheng, Vincent Chi Chung; Ip, Jonathan Daniel; Chu, Allen Wing Ho; Tam, Anthony Raymond; Chan, Wan Mui; Abdullah, Syed Muhammad Umer; Chan, Brian Pui Chun; Wong, Shuk Ching; Kwan, Mike Yat Wah; Chua, Gilbert T; Ip, Patrick; Chan, Jacky Man Chun; et al.
Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant BA.2 sublineage has increased rapidly in Europe and Asia since January 2022. Here, we report the epidemiological and genomic analysis of a large single-source BA.2 outbreak in a housing estate. Methods: We analyzed the epidemiological information on a community outbreak of BA.2 (STY outbreak). We performed whole viral genome sequencing using the Oxford Nanopore MinION device. We calculated the doubling time of the outbreak within a housing estate. Results: The STY outbreak involved a total of 768 individuals as of 5 February 2022, including 432 residents, visitors, or staff (56.3%) from a single housing estate (KC Estate). The outbreak at the KC Estate had a short doubling time of 1.28 days (95% confidence interval: .560–1.935). The outbreak was promptly controlled with the lockdown of 3 buildings within the housing estate. Whole-genome sequencing was performed for 133 patients in the STY outbreak, including 106 residents of the KC Estate. All 133 sequences from the STY outbreak belonged to the BA.2 sublineage, and phylogenetic analysis showed that these sequences cluster together. All individuals in the STY cluster had the unique mutation C12525T. Conclusions: Our study highlights the exceptionally high transmissibility of the Omicron variant BA.2 sublineage in Hong Kong, where stringent measures are implemented as part of the elimination strategy. Continual genomic surveillance is crucial in monitoring the emergence of epidemiologically important Omicron sublineages. Abstract : Using epidemiological and whole viral genome data, we demonstrated a single-source outbreak of Omicron variant sublineage BA.2 with a short doubling time in Hong Kong. This study highlighted the high transmissibility of BA.2 despite stringent prevention measures.